PENGARUH TERAPI RELAKSASI TARIK NAFAS DALAM TERHADAP PENURUNAN HIPERTENSI PADA LANSIA - Ahmad Arifin; Muhammad Iqbal Sutisna; Nayla Chairunnisa; Siva Silfiyana Aris; Gilda Titin Setiasih; Neng Afiffah; Destiyani Putri (MAJU : Indonesian Journal of Community Empowerment, 2026)
Hypertension in the elderly is a common health problem that can lead to serious complications if not managed properly. In addition to pharmacological therapy, a safe, easy-to-apply, and self-administered non-pharmacological approach is needed, one of which is deep breathing relaxation therapy. This community service activity aimed to determine the effect of deep breathing relaxation therapy on lowering blood pressure and increasing the independence of the elderly in managing hypertension. The method was descriptive, through health education and the application of deep breathing relaxation therapy on a 59-year-old female elderly person with a history of hypertension for two years. The intervention was carried out in two sessions with a duration of 5–15 minutes per session. Evaluation was conducted through blood pressure measurements before and after the intervention and interviews. The results showed a decrease in blood pressure and a reduction in complaints of anxiety and dizziness. The target was able to practice the therapy independently, thereby increasing comfort and self-control over hypertension.